Photobiomodulation Therapy Improves Inflammatory Responses by Modifying Stereological Parameters, microRNA-21 and FGF2 Expression: Photobiomodulation improves inflammatory responses - Amini, Abdollah; Ghasemi Moravej, Fahimeh; Mostafavinia, Atarodalsadat; Ahmadi, Hossein; Chien, Sufan; Bayat, Mohammad (Journal of Lasers in Medical Sciences, 2023)
Introduction: Photobiomodulation treatment (PBMT) is a relatively invasive method for treating wounds. An appropriate type of PBMT can produce desired and directed cellular and molecular processes. The aim of this study was to investigate the impacts of PBMT on stereological factors, bacterial count, and the expression of microRNA-21 and FGF2 in an infected, ischemic, and delayed wound healing model in rats with type one diabetes mellitus. Methods: A delayed, ischemic, and infected wound was produced on the back skin of all 24 DM1 rats. Then, they were put into 4 groups at random (n=6 per group): 1=Control group day4 (CG day4); 2=Control group day 8 (CG day8); 3=PBMT group day4 (PGday 4), in which the rats were exposed to PBMT and killed on day 4; 4=PBMT group day8 (PGday8), in which the rats received PBMT and were killed on day 8. The size of the wound, the number of microbial colonies, stereological parameters, and the expression of microRNA-21 and FGF2 were all assessed in this study throughout the inflammation (day 4) and proliferation (day 8) stages of wound healing. Results: On days 4 and 8, we discovered that the PGday4 and PGday8 groups significantly improved stereological parameters in comparison with the same CG groups. In terms of ulcer area size and microbiological counts, the PGday4 and PGday8 groups performed much better than the same CG groups. Simultaneously, the biomechanical findings in the PGday4 and PGday8 groups were much more extensive than those in the same CG groups. On days 4 and 8, the expression of FGF2 and microRNA-21 was more in all PG groups than in the CG groups (P<0.01). Conclusion: PBMT significantly speeds up the repair of ischemic and MARS-infected wounds in DM1 rats by lowering microbial counts and modifying stereological parameters, microRNA-21, and FGF2 expression.